2020
DOI: 10.3390/su12229414
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Quantitative Demographic Potential—A Comparative Study of Polish–German and Polish–Lithuanian Transborder Regions

Abstract: Demographic potential is a particularly important consideration in border areas that are peripheral regions of a country. The aim of this study was to identify differences in the quantitative demographic potential of Polish–German and Polish–Lithuanian transborder regions, as well as the extent to which natural population increase and net migration influence the demographic potential of border regions. An essential element of the research was the analysis of the importance of borders on shaping the quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…The spatial analysis of the relationship clearly implies that at the onset of the epidemic (30 April 2020), the highest dependency (high WO and prevalence) in Poland was noted primarily in rural areas near urbanized and industrial zones adjacent to big cities. This relationship reflects the functional and spatial structure [ 39 ]. In November 2020 (end of the first epidemic wave) the disease moved to the remaining rural areas and a clear correlation was noted between the classification of areas according to their vulnerability to epidemic threat and the number of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The spatial analysis of the relationship clearly implies that at the onset of the epidemic (30 April 2020), the highest dependency (high WO and prevalence) in Poland was noted primarily in rural areas near urbanized and industrial zones adjacent to big cities. This relationship reflects the functional and spatial structure [ 39 ]. In November 2020 (end of the first epidemic wave) the disease moved to the remaining rural areas and a clear correlation was noted between the classification of areas according to their vulnerability to epidemic threat and the number of cases.…”
Section: Discussionmentioning
confidence: 99%
“…It took into account demographic, social, economic and spatial development factors indirectly reflecting the level of interpersonal relations and social interaction. Previous studies deemed them as determinants of the spread of pandemics, including COVID-19 [ 37 , 38 ], with new elements [ 39 ]. The factors were also assigned—according to types of interpersonal and social relations—to two groups: intended and unintended interactions.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature [44][45][46][47] revealed that not all new housing estates in Poland are designed in a planned and rational manner. Many MFREs, in particular in suburban areas, are characterized by chaotic development.…”
Section: Large-scale Prefabricated Buildingmentioning
confidence: 99%
“…The research results may help planners and representatives of regional self-governments implement EU social policy, including cross-border cooperation. The research problem undertaken in the article extends the scope of research conducted by the authors in the border regions of Poland (Gwiaździńska-Goraj et al, 2020;Pawlewicz et al, 2020;Thöle & Jezierska-Thöle., 2019).…”
Section: Introductionmentioning
confidence: 99%